Fetal Aortic Dysmorphogenesis and Maternal Diabetes: Decoding the Molecular Signaling Pathways Towards New Therapeutic Targets - Alabdulgader, Abdullah (Archives of Clinical and Biomedical Research, 2025)
Morphogenesis in biology represent miraculous fact of our life on the planet. Decoding the mysteries of morphogenesis and the struggle to solve the complexity of the puzzle of creature started very late in human species time line. Deviation in the normal developmental steps of morphogenesis result in congenital anomalies which constitute leading cause of death in most world countries. The most common congenital anomaly is congenital malformation of the human heart. Until the moment, most of the causes of congenital heart diseases (CHDs) are still, obscure and unknown. CHD constitute major health ,social ,psychological and economic burden on individuals , families as well as world communities and nations. The most accurate illuminator to solve the puzzle of causes of diseases is epidemiology. Epidemiology must be the guiding force towards the different scientific directions to fight diseases. The study of the cellular and molecular pathogenesis of heart valve disease is an emerging area of research made possible by the availability of cultures of valve interstitial cells (VICs) and valve endothelial cells (VECs) and by the design and use of in vitro and in vivo experimental systems that model elements of valve biological and pathobiological activity. The wisdom derived from the up to date scientific literature dectate more gobal perspect of aortic valve disease. Congenital aortic valve stenosis most commonly due to bicuspid aortic valve stenosis(BCAS) and Calcific Aortic Valve Disease (CAVD) are continuum of one common stem of pathology. Towards the dream of aborting the process of cardiac dysmorphogenesis in human, we established a nation wide epidemiological project devoted to discover genetic and environmental risk factors of CHD. The philosophy of the project was to adopt etiological perspective based on collecting massive genetic and environmental data on each CHD subtype, followed by statistical management to establish statistical correlations towards investigating causeeffect relationship. Although, it is well known that maternal diabetes is very important risk factor for CHD in all world nations, the operating cellular and molecular signaling pathways ending up with BCAS are still elusive. This paper is an atempt to explore the dynamics of cellular and molecular signaling involved with BCAS in maternal diabetes, toward the path of suggesting possible therapeutic as well as preventive measures of aortic valve disease in human species.